The only child - Guojing, 1983- (New York : Schwartz & Wade Books, 2015)
In this wordless graphic novel, a young girl traveling from her city apartment to her grandmother's country home becomes lost and enters a fantastical world in the clouds.
Keywords: Lost children -- Fiction; Adventure and adventurers -- Fiction; Stories without words; Graphic novels